WATER RESOURCES SUSTAINABILITY AT SÃO MIGUEL DO ANTA COUNTY,MINAS GERAIS, BRAZIL: A SYSTEM DYNAMICS APPROACH. - GONZÁLEZ, A.M.G. ORELLANA; DA SILVA JR., A. G.; SÁNCHEZ-ROMÁN, R. M.; SILVA, E.; BRAGA, J. L. (Revista Brasileira de Engenharia de Biossistemas, 2008)
The equilibrium between agricultural activities and rational land use, economic developmentandwater resources demandis the key factorrelated to biodiversity preservation and minimumenvironmental impact in São Miguel do Anta County, Minas Gerais State, Brazil.This work analyzesthe consequences of life quality improvement of low-incomerural families beneficiary of a federalfinancing program, and its effects on ecology, environment and water resources sustainability.Amodel was implemented, assessing water demand, total annual loads, originated from human andagricultural activities. Five scenarios were established, considering climate changes and irrigationpractices. Results show the possibility of evaluating the consequences of public policies in economy,ecology and sustainability